Perbedaan Pengetahuan Ibu Sebelum Dan Sesudah Diberikan Penyuluhan Tentang ASI Eksklusif Di Kelurahan Lansot Kota Tomohon Provinsi Sulawesi Utara - Ampow, Miracle Eukharistia; Sanggelorang, Yulianty; Mawo, Florianus Hans Matheus; Maya, Anugrah; Tambuwun, Brevina Ostofin; Arbie, Astrid Razkia; Corputty, Stevanny; Mandanusa, Mita Prasetia; Timpal, Bill Farel; Regar, Sweetie Avril; Pasongka, Dian Pratiwi (-, 2025)
The main benefit of exclusive breastfeeding is that it supports both brain and physical development in infants. This is because, from birth to six months of age, babies should receive nutrition exclusively from breast milk. According to the 2018 Basic Health Research, only 37.3% of infants in Indonesia received exclusive breastfeeding, while in North Sulawesi Province, the coverage of exclusive breastfeeding in 2018 reached 64.95%. This relatively low percentage is primarily due to socio-cultural factors and a lack of awareness among pregnant mothers regarding the importance of exclusive breastfeeding. One effective method to improve maternal health knowledge is through education.This study aims to assess the difference in maternal knowledge before and after an intervention in the form of a health education session on exclusive breastfeeding in Lansot Village, Tomohon City, North Sulawesi Province. The intervention was conducted on August 26, 2024, in the form of an educational session on exclusive breastfeeding. Post-test results indicated a significant improvement in the knowledge of mothers who attended the session regarding the importance of exclusive breastfeeding for infants aged 0–6 months.